2020
DOI: 10.1182/bloodadvances.2020003632
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in murine erythropoiesis from birth to adulthood: implications for the study of murine models of anemia

Abstract: Liver, spleen, and bone marrow are 3 key erythropoietic tissues in mammals. In the mouse, the liver is the predominant site of erythropoiesis during fetal development, the spleen responds to stress erythropoiesis, and the bone marrow is involved in maintaining homeostatic erythropoiesis in adults. However, the dynamic changes and respective contributions of the erythropoietic activity of these tissues from birth to adulthood are incompletely defined. Using C57BL/6 mice, we systematically examined the age-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…The role of the spleen in supporting erythropoiesis during the postnatal period has received little attention. While this paper was being revised Chen et al (2021) published a paper on spleen erythropoiesis in developing mice which supports our results. We have shown that in the spleen a significant decrease in erythroid precursors are seen at about 4 weeks of age.…”
Section: Discussionsupporting
confidence: 85%
“…The role of the spleen in supporting erythropoiesis during the postnatal period has received little attention. While this paper was being revised Chen et al (2021) published a paper on spleen erythropoiesis in developing mice which supports our results. We have shown that in the spleen a significant decrease in erythroid precursors are seen at about 4 weeks of age.…”
Section: Discussionsupporting
confidence: 85%
“…(71) In mice the spleen can support stress erythropoiesis in response to acute anemia, (72) and is an active site of erythropoiesis in the first weeks after birth until steady-state erythropoiesis is established in the BM. (73) The findings in the spleen are in striking contrast to the thymus, where T cell precursor differentiation appears to proceed normally in PTH1R-OsxKO mice. Early T cell precursors, derived from common lymphoid progenitors, differentiate in the thymus into mature CD4 and CD8 T cells.…”
Section: Discussionmentioning
confidence: 94%
“…As discussed in more detail below, cell size and Hb content might not only be influenced by the maturation stage of erythroid cells, but also by the developmental wave of human erythropoiesis [ 12 ]. Besides different growth kinetics and altered expression of transcription factors during erythropoiesis [ 32 , 33 ], fetal liver-derived RBCs like CB cells are described to have a higher volume and Hb content in comparison to BM-derived adult RBCs [ 10 , 11 ]. Interestingly, the Hb concentration in adult nRBCs was lower than in cRBC_iPSC and CB-derived nRETs, but comparable to cRBCs derived from adult HSPCs (cRBC_adult) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas CB cells originate from fetal liver erythropoiesis, PB cells originate from adult bone marrow (BM) erythropoiesis. There is increasing evidence that RBCs from different developmental waves differ in their cellular features like hemoglobin (Hb) composition, Hb content, and cell size [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%